TINJAUAN PENERAPAN REKAM MEDIS ELEKTRONIK DI DALAM REGISTRASI PASIEN RAWAT JALAN UPTD PUSKESMAS CIPAYUNG DEPOK - Garis Gemilang; Reza Kurniawan (MEDICORDHIF Jurnal Rekam Medis, 2023)
Based on observations of SIMPUS at the UPTD Puskesmas Cipayung Depok, the new patient registration module already running quite well, but it is not yet in accordance with the variable guidelines and meta data for electronic medical records, in which the variable guidelines and meta data for electric medical records are meant to be used as standard data elements for ease of compatibility and/or interoperability of data in electronic systems developed by health care facilities. This journal is based on research data collected on January 2023 with a descriptive research method and by collecting data by observation and interviews. With the results of the research conducted, it was found that the early development of the electronic medical record system at the Cipayung Health Center UPTD was started at the end of 2014 and continued with the development of online registration in 2018. Obstacles that still occur frequently and have not been resolved to date are bugs that have appeared, and there is yet a standardization in the application of variables and metadata used in accordance with the guidelines for variables and metadata of electronic medical records. The suggestions given is to adjust the standard variables and metadata, improve the system to avoid bugs, and standardizing variables.